Effects of Vitex Agnus Castus Leave Extract on Induced Retinal Angiogenesis in Rabbit - Sara Wathiq Hadi; Shihab Abdulrahman Shihab (Institute of Medico-legal Publications Pvt Ltd, 2021)
Retinal pathologic angiogenesis is the leading cause of blindness in human generate from age-relatedmacular degeneration (AMD), diabetic retinopathy and premature retinopathy (ROP).The aim of this studyis to investigate the effect of vitex agnus castus leave extract on induced retinal angiogenesis in rabbitsby intravitreal injection of VEGF. Alcoholic extract of vitex agnus castus prepared and formulated forintravitreal injection. Twenty four pigmented rabbits included in this study and allocated into four equalgroups(6 rabbits in each group): Retinal angiogenesis induced group, group treated by bevacizumab, grouptreated by 100mcg of Vitex agnus castus leave extract, and group treated by 50mcg of Vitex agnus castusleave extract as intravitreal injection. Parameters include matrixmetalloproteinase-9, intracellular adhesionmolecule-1. The result of the current study revealed that intravitreal injection of Vitex agnus castus leaveextract was reduced the level of MMP-9 and ICAM-1 in comparison with retinal angiogenesis inducedgroup after one week of retinal angiogenesis induction , although it was non-significant (P>0.05).